Expression of selected groups of pathogenesis-related (PR) proteins at early stage of Ganoderma boninense infection of oil palm (Elaeis guineensis Jacq.) seedlings - Ramli, Redzyque Ramza; Abdullah, Siti Nor Akmar; Abdul Bahari, Mohammad Nazri; Mohd Sakeh, Nurshafika (Institute of Plantation Studies, Universiti Putra Malaysia, 2017)
Basal stem rot (BSR) is a major fungal disease of the oil palm (Elaeis guineensis Jacq.) caused by the pathogenic fungi of the Ganoderma spp. which degrade plant cell wall components. The information on molecular response of oil palm to these pathogens are still limited, even though it is crucial to develop a better strategy in handling and eliminating BSR. The most prevalent and virulent species associated with BSR is Ganoderma boninense. However, poor understanding of the defence response in oil palm towards this necrotrophic fungus has complicated the resolving measures. Early detection of Ganoderma attacks in oil palm where physical symptoms have not yet appeared can offer opportunities to prevent the spread of this necrotrophic fungi. Hence, characterization of defence-related molecular changes and production of anti-fungal agents during early interaction with G. boninense is of utmost important. In order to have a better understanding of the defence mechanisms deployed by oil palm against G. boninense, we compared the pathogenesis related proteins production of uninoculated with G. boninense inoculated oil palm seedlings. Oil palm (Elaeis guineensis) seedlings were artificially infected with G. boninense inoculums and RNA samples were taken from root tissues at different stages within less than 2 weeks post infection (0, 3, 7, 11 days after infection) and used for RNA-Seq analysis. Differential gene expression (DEGs) analyses displayed induced expression of genes encoding various types of PR proteins including a few classes of PR proteins that have not been previously reported, which can potentially be an important component of the complex defence machinery deployed by oil palm against G. boninense.